Pengaruh Kinesio Taping dan Deep Transverse Friction Terhadap Penurunan Nyeri Kasus Carpal Tunnel Syndrome pada Pekerja Pabrik Rokok - Romadhona, Laila; Widodo, Agus (Journal of Health and Therapy, 2023)
Carpal tunnel syndrome is an extremity disorder caused by narrowing of the carpal tunnel resulting in pressure on the median nerve at the wrist. The occurrence of irritation of the median nerve that causes tingling and numbness of the thumb, index, and middle fingers due to swelling or a change in the position of the tissue in the carpal tunnel compresses and irritates the median nerve. The process of working cigarette factory workers to pack cigarettes using traditional manual work methods by hand, can cause complaints of carpal tunnel syndrome. So, the purpose of this research is to find out how the effect of Kinesio Taping and Deep Transverse Friction with Carpal tunnel syndrome in the Packaging Section of a Cigarette Factory. This study was a quasi experimental research on the effect and symptoms of Kinesio Taping and Deep Transverse Friction for Carpal tunnel syndrome cases. Kinesio Taping stabilizes muscles, joints and improves blood circulation thereby reducing pain. Deep Transverse Friction increases range of motion reducing pain. The research subjects were all cigarette packaging workers who have Carpal tunnel syndrome case, totaling 20 people. Measurements to assess the pain scale using Boston Carpal tunnel syndrome. The results of the test of the effect of Kinesio Taping and Deep Transverse Friction showed by the p-value = 0.005 and 0,000 (p<0.05), so there are reducing pain in Kinesio Taping groups and Deep Transverse Friction groups. But there was not different of Kinesio Taping groups and Deep Transverse Friction groups on reducing carpal tunnel syndrome pain, showed by the p-value = 1,000 (p>0,005). The conclusion of this study, there is a significant relationship between Kinesio Taping and Deep Transverse Friction on reducing carpal tunnel syndrome pain in workers at the Djarum cigarette factory, but was not different of Kinesio Taping groups and Deep Transverse Friction groups on reducing pain.